Immunotherapy, targeted therapy, and their cross talks in hepatocellular carcinoma - Liu, Jun; Park, Kevin; Shen, Ziyang; Lee, Hannah; Geetha, Purnima; Pakyari, Mohammadreza; Chai, Li (Frontiers in Immunology, 2023)
Hepatocellular carcinoma (HCC) is a challenging malignancy with limited treatment options beyond surgery and chemotherapy. Recent advancements in targeted therapies and immunotherapy, including PD-1 and PD-L1 monoclonal antibodies, have shown promise, but their efficacy has not met expectations. Biomarker testing and personalized medicine based on genetic mutations and other biomarkers represent the future direction for HCC treatment. To address these challenges and opportunities, this comprehensive review discusses the progress made in targeted therapies and immunotherapies for HCC, focusing on dissecting the rationales, opportunities, and challenges for combining these modalities. The liver's unique physiology and the presence of fibrosis in many HCC patients pose additional challenges to drug delivery and efficacy. Ongoing efforts in biomarker development and combination therapy design, especially in the context of immunotherapies, hold promise for improving outcomes in advanced HCC. Through exploring the advancements in biomarkers and targeted therapies, this review provides insights into the challenges and opportunities in the field and proposes strategies for rational combination therapy design.